Arteterapia en Argentina: una historia, un relato, una versión - Farias, Adriana (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2007)
The narration of the theoretical construction of some of the principles supporting the formation of Art Therapy Specialists (a Post-Degree Career of the National University Institute for the Arts, IUNA) in Argentina is offered here, together with its Director`s experience as an Art Therapist at the Day Hospital (Ambulatory Attention Service) of “José T. Borda” Psychological Assistance Hospital, since 1997.